Hippocampal microglial activation and glucocorticoid receptor down-regulation precipitate visceral hypersensitivity induced by colorectal distension in rats. (March 2016) - Zhang, Gongliang; Zhao, Bing-Xue; Hua, Rong; Kang, Jie; Shao, Bo-Ming; Carbonaro, Theresa M.; Zhang, Yong-Mei
Abstract: Visceral hypersensitivity is a common characteristic in patients suffering from irritable bowel syndrome (IBS) and other disorders with visceral pain. Although the pathogenesis of visceral hypersensitivity remains speculative due to the absence of pathological changes, the long-lasting sensitization in neuronal circuitry induced by early life stress may play a critical role beyond the digestive system even after complete resolution of the initiating event. The hippocampus integrates multiple sources of afferent inputs and sculpts integrated autonomic outputs for pain and analgesia regulation. Here, we examined the hippocampal mechanism in the pathogenesis of visceral hypersensitivity with a rat model induced by neonatal and adult colorectal distensions ( CRD s). Neither neonatal nor adult CRD evoked behavioral abnormalities in adulthood; however, adult re-exposure to CRD induced persistent visceral hypersensitivity, depression-like behaviors, and spatial learning impairment in rats that experienced neonatal CRD . Rats that experienced neonatal and adult CRD s presented a decrease in hippocampal glucocorticoid receptor (GR) immunofluorescence staining and protein expression, and increases in hippocampal microglial activation and cytokine (IL-1β and TNF-α) accumulation. The decrease in hippocampal GR expression and increase in hippocampal IL-1β and TNF-α accumulation could be prevented by hippocampal local infusion of minocycline, a microglial inhibitor. These results suggest that neonatal CRD can increase the vulnerability of hippocampal microglia, and adult CRD challenge facilitates the hippocampal cytokine release from the sensitized microglia, which down-regulates hippocampal GR protein expression and, subsequently, precipitates visceral hypersensitivity. Highlights: Microglia and hippocampus participate in visceral hypersensitivity. Influence of hippocampal microglia on visceral hypersensitivity remains elusive. Colorectal distension induces visceral hypersensitivity and GR down-regulation. Inhibition of hippocampal microglial activation suppresses visceral hypersensitivity.